Peningkatan Produktivitas Kedelai Pada Lahan Sub Optimal Lampung Akibat Pemberian Mulsa Dan Pembenah Tanah - Umi Haryati; Ishak Juarsah (Jurnal WACANA PERTANIAN, 2020)
The research was carried out on Ultisol soil in Sukadana Village, Sukadana District, East Lampung Regency. The research objective was to determine Soybean Productivities Improvement in Suboptimal Land Due application of Mulch and Soil Conditioner. The plant indicator used was the soybean variety of Anjasmoro with a spacing of 40 cm x 15 cm.  The research used a split plot design with three replications. Mulching treatments (without mulch and mulch of maize crops residue 10 t ha-1) as main plot  and and soil conditioner (control, Biochar I/SP 50 2,5 t ha-1, Beta 2,5 t ha-1, Biochar II/husk charcoal 2,5 t ha-1 , and manure  5 t ha-1) as subplot.  The variables observed in this research were plant grouwth and yield.  The results showed that the application of mulch residue from corn plants did not affect the development of soybean roots, however, soil conditioner increased the weight and root length of soybean plants. Biochar I and Beta improveers have the best effect on root weight and length. Mulch residue of maize plants and soil conditioner did not significantly affect soybean crop yield. The soil conditioner  increased the yield of soybean dry seeds and the soil repairer Biochar II (husk charcoal) 2.5 t ha-1 and manure 5 t ha-1 gave the best soybean dry seed yields